H.L. Mencken - American Writers 62 : University of Minnesota Pamphlets on American Writers - Wagner, Philip M. (Philip Marshall), 1904-1996 (Book collections on Project MUSE., 1966)
H.L. Mencken - American Writers 62 was first published in 1966. Minnesota Archive Editions uses digital technology to make long-unavailable books once again accessible, and are published unaltered from the original University of Minnesota Press editions.